2007
DOI: 10.1016/j.nuclphysa.2006.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Conical Flow from Quenched Jets in sQGP

Abstract: Starting with a reminder of what is strongly coupled Quark-Gluon Plasma (sQGP), we proceed to recent advances in jet quenching and heavy quark diffusion, with a brief summary of various results based on AdS/CFT correspondence. The conical flow is a hydrodynamical phenomenon created by energy and entropy deposited by high energy jets propagating in matter, similar in nature to well known sonic boom from the supersonic planes. After a brief review, we discuss excitations of two hydro modes -sound and "diffusion"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…In interesting followup work, the authors of [28,29,30] studied the profile of the coherent gluonic fields set up by the joint quark-plasma system, which are responsible for taking energy away from the moving quark. Their results appear to be consistent with phenomenological expectations of 'conical flow' [31].…”
supporting
confidence: 84%
See 1 more Smart Citation
“…In interesting followup work, the authors of [28,29,30] studied the profile of the coherent gluonic fields set up by the joint quark-plasma system, which are responsible for taking energy away from the moving quark. Their results appear to be consistent with phenomenological expectations of 'conical flow' [31].…”
supporting
confidence: 84%
“…In interesting followup work, the authors of [28,29,30] studied the profile of the coherent gluonic fields set up by the joint quark-plasma system, which are responsible for taking energy away from the moving quark. Their results appear to be consistent with phenomenological expectations of 'conical flow' [31].An important measure of energy loss used in phenomenological models of mediuminduced radiation (for reviews see [32]) is the jet-quenching parameterq, defined as the average squared transverse momentum transferred to the quark by the medium, per unit distance travelled. The authors of [33] suggested thatq could be identified with the logarithm of a certain lightlike Wilson loop, 3 and then used AdS/CFT to compute the latter for N = 4 SYM.…”
supporting
confidence: 74%
“…We note however, that in the large N c limit 21) with no additional derivative corrections. This follows from the fact that the linearized hydrodynamic expressions for the conserved densities ∆T 0ν hydro , as given in Eqs.…”
Section: A Equations Of Motion and Effective Sourcementioning
confidence: 72%
“…Analysis of the distribution and correlations in produced jets can provide information about the dynamics of the plasma, including the rates of energy loss and momentum broadening of quarks traversing the plasma [21,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…(See, for example, Refs. [12,13,14,15,16,17,18,19,20,21,22,23,24,25], and references therein.) At least for some quantities, this is quite successful.…”
Section: Introductionmentioning
confidence: 99%